Adsorption Of Dye From Household Industrial Wastewater Of Samarinda Seberang Weaving Gloves Using Adsorbent From Activated Charcoal Lai Fruit Powder (Durio Kutejensis (Hassk.) Becc.) - Sari, Riska Alif Kartika; Wirawan, Teguh; Sitorus, Saibun (Jurusan Kimia FMIPA UNMUL, 2024)
Textile dyes include compounds that are difficult to decompose naturally. In the waters is a serious environmental problem because it can have a negative impact. This study aims to utilize lai fruit peel which is used as activated charcoal as an adsorbent to adsorb purple dyes in woven sarong waste water. The first stage of making activated charcoal is through carbonation in a furnace at 500oC for 30 minutes. Activation was carried out chemically by immersing it in 2 M H2SO4 solution for 24 hours. FTIR characterization of the resulting activated carbon was carried out to determine its functional groups and SEM characterization to determine its morphology. The results of FTIR characterization of activated carbon from lai fruit peel powder have functional groups -CO- and –OH, while SEM characterization of activated carbon from lai fruit peel powder is in the form of fibers with open pore surfaces that are spread on the surface and cavity walls of the activated charcoal of lai fruit peel powder. The adsorption process was carried out using the bath method and the concentration of the purple dye was determined using a UV-Vis spectrophotometer. The results showed that the adsorption of purple dye by activated charcoal was optimal at contact time of 1 minute and at pH 8. Adsorption of purple dye followed by the Freundlich adsorption pattern and had a maximum chemical adsorption capacity of 55.209 mg/g.